Exploring the Interaction Between eIF2α Dysregulation, Acute Endoplasmic Reticulum Stress and DYT1 Dystonia in the Mammalian Brain. (10th February 2018) - Beauvais, Genevieve; Rodriguez-Losada, Noela; Ying, Lei; Zakirova, Zuchra; Watson, Jaime L.; Readhead, Ben; Gadue, Paul; French, Deborah L.; Ehrlich, Michelle E.; Gonzalez-Alegre, Pedro
Highlights: Human iPSC-derived neurons exhibit a dynamic dose–response to tunicamycin. TorsinA is post-translationally stabilized by acute ER stress in different model systems. Transgenic DYT1 rats exhibit an abnormal response to tunicamycin. There is eIF2α dysregulation in embryonic homozygous DYT1 knock in mice brain. Abstract: DYT1 dystonia is a neurological disease caused by dominant mutations in the TOR1A gene, encoding for the endoplasmic reticulum (ER)-resident protein torsinA. Recent reports linked expression of the DYT1-causing protein with dysregulation of eIF2α, a key component of the cellular response to ER stress known as the unfolded protein response (UPR). However, the response of the DYT1 mammalian brain to acute ER stress inducers has not been evaluated in vivo . We hypothesized that torsinA regulates the neuronal UPR and expression of its mutant form would alter this process. TorsinA was post-transcriptionally upregulated upon acute ER stress in different models, suggesting a role in this response. Moreover, increased basal phosphorylation of eIF2α in DYT1 transgenic rats was associated with an abnormal response to acute ER stress. Finally, an unbiased RNA-Seq-based transcriptomic analysis of embryonic brain tissue in heterozygous and homozygous DYT1 knockin mice confirmed the presence of eIF2α dysregulation in the DYT1 brain. In sum, these findings support previous reports linking torsinA function, eIF2α signaling and the neuronal response to ER stress in vivo . Furthermore, we describe novel protocols to investigate neuronal ER stress in cultured neurons and in vivo .